The management of waqf in India with a special reference to Delhi Waqf Board : a critical analysis - Ali, Jawwad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study examines the issues which are obstacles for the development of Waqf institution in Delhi Waqf Board as reported by the Sachar Committee in 2006 along with identification of other issues which were not mentioned by this Committee. The study drives its importance from the fact that Waqf aids the objective of creating global socio-economic well-being among the Muslim community, by promoting a system which enables the needy, poor, and helpless to a proportion of the capital in the ownership of the wealthy. Waqf Properties in Delhi account to thousands of square meters of land. However, the benefit of the Waqf has not lived up to the expectations of society due to misuse of these properties by those who were the guardian of these properties or those who implemented the Waqf law. The study used the qualitative, and analytical research methods which involved gathering information through interview. The study concludes that at the present, the management of Waqf properties is considerably impaired due to high frequency of litigation and poor management. Importantly, the root cause of the deterioration of this Board is encroachment of Waqf properties specially by the private and government Bodies. Additionally, negligence of Mutawalli and financial problem etc., are obstacles for the development of the Waqf institution in Delhi. The study highlights that the government authorities and members of Waqf Board are themselves involved in occupying Waqf properties. In addition, due to mismanagement of Waqf properties, Delhi Waqf Board is not able to generate incomes to protect the Waqf properties from illegal occupation and to fulfill the objective of Waqf. Moreover, the study found the reasons behind the issues which have been negatively impacting the Waqf institution such as lack of proper management by authorities of Board, ineffectiveness of legal department and contradiction between State Government and Lieutenant Governor (LG). Finally, the researcher proposes Shari'ah governance framework for the Delhi Waqf Board to deal with these issues. The researcher also proposes that Waqf Protection Committees, consisting of conscientious members from the local Muslim community, should be formed to keep a watch over the affairs of the local Awqaf properties.